Probing organ structure, function and physiology using Quantitative Magnetic Resonance Imaging techniques - Bradley, Christopher (2023)
This thesis outlines four first author peer reviewed journal articles and three co-author peer reviewed journal articles submitted by the author for the award of the research degree Doctor of Philosophy by Published Works to the University of Nottingham. The focus of these works is to use novel Magnetic Resonance Imaging (MRI) techniques to probe the physiology of abdominal organ structure and function in healthy volunteers and patients with liver disease. The key aims of these published works were to: (Publication I) Cross sectionally delineate liver disease using MRI; (Publication II) Compute serial measures of the variation in quantitative MRI measures to understand the repeatability to aid the interpretation of data in future studies of clinical trials of drugs and interventions for disease progression; (Publication III) Use MRI to detect short terms changes to liver architecture in disease using a drug intervention; (Publication IV) Use MRI in healthy volunteers to dynamically observe changes to organ function during fluid infusions (colloid and crystalloid), to mimic the infusions typically used in gastrointestinal and liver surgery. Publication I, titled ‘Multi-organ assessment of compensated cirrhosis patients using quantitative magnetic resonance imaging’, assessed multiple organs (heart, liver, kidneys, spleen and splanchnic systemic circulation) in a cohort of patients with liver disease in a single one hour scan session. This work showed that quantitative MRI measures have the power to predict negative liver related outcomes up to 2304 days before the event occurred. Publication II, titled ‘Variability of Non-invasive MRI and Biological Markers in Compensated Cirrhosis: Insights for Assessing Disease Progression’ collected multiple organ (heart, liver, kidneys, spleen) serial quantitative MRI measures annually over a 3-year period in patients with severe but stable liver disease, and reports on the variability of these MRI measures. In this paper the annual variance in MRI measures is used to provide sample size calculations for prospective interventional studies investigating cirrhosis regression. Publication III, titled ‘Short-term changes observed in multiparametric liver MRI following therapy with direct-acting antivirals in chronic hepatitis C virus patients’, shows that quantitative MRI measures of the liver are sensitive enough to observe changes to liver structure in a 3-month window between pre- and post- treatment of a direct acting antiviral therapy in patients with chronic hepatitis C virus who achieved sustained virological response. Publication IV, titled ‘A randomized, controlled, double-blind crossover study on the effects of isoeffective and isovolumetric intravenous crystalloid and gelatin on blood volume, and renal and cardiac hemodynamics’ showed that cardiac and renal quantitative MRI measures could detect haemodynamic changes over the time course of different crystalloid and colloid fluid infusion regimes typically used in gastrointestinal and liver surgery. There were no differences between infusion types despite the volume of a crystalloid infusion being three times that of one of the colloid infusions. These research articles all applied MRI to evaluate abdominal organ physiology and present novel findings. Three further co-authored publications are also briefly described. Publication V, titled ‘Non-invasive assessment of portal hypertension using quantitative magnetic resonance imaging. Journal of hepatology’ demonstrated that quantitative structural and haemodynamic MRI measures can be used together to create a model that predicts portal pressure measurements, so MRI measures could be used as a surrogate for the hepatic venous pressure gradient (HVPG) procedure in patients with liver disease. This model was then applied to a validation cohort as proof of concept. Publication VI, ‘Multiparametric renal magnetic resonance imaging: validation, interventions, and alterations in chronic kidney disease. Frontiers in physiology’ described a multiparametric quantitative MRI protocol for the assessment of the kidneys with recommendations for best practices and short term validation of measures. Publication VII, ‘In silico evaluation and optimisation of magnetic resonance elastography of the liver’ used magnetic resonance elastography (MRE) simulations to evaluate current MRE techniques and offered optimisations to improve accuracy of MRE data acquisition and analysis.